Nutritional supplements in Norwegian elite athletes-impact of international ranking and advisors. - Sundgot-Borgen, J.; Berglund. B.; Torstveit, M. K. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The aims of this study were to investigate (a) the use of nutritional supplements (NS) (vitamins, minerals, Omega 3, antioxidants, ginseng, amino acids, Creatine and energy supplements) in elite athletes of different international ranking (b) why athletes are using NS, and (c) who recommends the elite athletes to use NS. The total population of elite athletes in Norwegian National Teams (n = 1620, 960 males and 660 females aged 15-39 years) and randomly selected (n = 1681) (916 males and 765 females) controls from the general population, were given a questionnaire including questions about use of nutritional supplements (NS), and from whom athletes had received information about nutrition and recommendations to use NS. The response rate was 76% for male and 92% for female athletes and 75% and 81% for male and female controls, respectively. A similar percentage of female athletes (54%) and controls (52%) reported use of one or more NS, but more male athletes (51%) than male controls (32%) used NS (P < 0.001). However, independent of gender, more athletes as compared to controls used minerals (males 26% vs. 8%; females 42% vs. 20%), amino acids (males 12% vs. 4%; females 3% vs. 0), and Creatine (males 12% vs. 2%; females 3% vs. 0). A lower percentage of NS users were observed in the best female athletes (52%) as compared to female athletes with less experience of international competition (73%) (P < 0.01). In male athletes, NS use was independent of international ranking (49%-53%). The coach was the main advisor for use of NS for both male (58%) and female athletes (52%). For male and female athletes, the main reason for using NS was that they felt it was needed in addition to their daily intake (56% and 67%, respectively). Forty one percent of the male and 37% of the female athletes using NS felt they were well informed about nutrition in general and NS. However, 8% of the NS users did not know whether the NS they used was doping classified or not. In conclusion: we found that a similar percentage of female elite athletes and controls, but a higher percentage of male elite athletes than controls, reported the use of NS. There was a lower percentage of NS use among the top female athletes, but not the top male athletes as compared to the less successful elite athletes. The coach was the main advisor for NS use both for male and female elite athletes.